2008
DOI: 10.1007/s10658-008-9272-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of Plum pox virus isolates in the Czech Republic

Abstract: Plum pox virus (PPV), the causal agent of Sharka disease, is an important pathogen of stone fruit trees. In this study, 24 new Czech PPV isolates from five different orchards were collected and characterized, molecularly. PPV-D isolates were identified in all orchards studied; whereas PPV-Rec isolates were identified in only two of them. A phylogenetic analysis on (Cter) NIb-(Nter) CP was performed. Three Czech PPV-D isolates BOH11CZ, BOH12CZ, and BOH13CZ diverged into a significantly separated cluster. PPV-Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…There are several global studies of the population structures of RNA viruses of human and other animals, but few of those of plants [36,37]. Several papers have been published reporting sequence analyses of regional populations of PPV [38][39][40][41], allowing the local spread and evolution of particular strains to be identified [42][43][44]. Despite these efforts, the global structure of the PPV population has not yet been determined, although it is now possible, as currently (January 2019) there are more than 200 complete genomic sequences of various isolates of PPV available in the GenBank database (https://www.…”
Section: Introductionmentioning
confidence: 99%
“…There are several global studies of the population structures of RNA viruses of human and other animals, but few of those of plants [36,37]. Several papers have been published reporting sequence analyses of regional populations of PPV [38][39][40][41], allowing the local spread and evolution of particular strains to be identified [42][43][44]. Despite these efforts, the global structure of the PPV population has not yet been determined, although it is now possible, as currently (January 2019) there are more than 200 complete genomic sequences of various isolates of PPV available in the GenBank database (https://www.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular variability of some Czech Plum pox virus isolates was studied by Navrátil et al (1998), but in this paper it was not described how and where the isolates were sampled; it was only reported that some of them originated from our institute (RICP Prague), only one case of mixed infection was found, and PPV-D isolates prevailed. Recently, Gadiou et al (2008) studied 24 Czech PPV isolates from five different plum orchards situated in Moravia. PPV-D isolates were identified in all orchards, PPV-Rec only in two of them.…”
Section: Resultsmentioning
confidence: 99%
“…The sequencing BYMV was started from the primers which were covering mainly CP-NIb gene (Oertel et al, 1997;Lecoq et al, 2000). Sequencing of CP and NIb genes is often used for phylogenetic analyses of many species of the genus Potyvirus (Handley et al, 1998;Alegria et al, 2003;Gadiou et al, 2008;Wylie and Jones, 2009;Campos et al, 2014). Several techniques for detecting BYMV are now available ELISA, dot-blot hybridization, sequencing and PCR seemed to be the most promising technique for detection of low amounts infected plants of BYMV (Scott et al, 1989;Efaisha, 2005;Ganesh et al, 2009a;Choi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%